Ação comunicacional da quitosana: o percurso social da inovação - Leite, Sandra Nunes (Universidade do Vale do Rio do Sinos, 2006)
The thesis proposes an analysis about the interaction between the scientific laboratory and its social context by focusing on the media processes that take place in the production of technological innovations. Due to the multiplicity of agents involved in the course of innovation, which are identified in the study case, this thesis intends to show that the invention process requires differentiated ways of communicational interactions so that the relocation from laboratory to society may transform the invention into innovation. Thus, it designs the social space of the technological innovation that comes from chemical and pharmacological researches, and which is permeated into cultural, political, symbolic and media aspects. Inspired by the wondering of how interactions take place in the dispute of innovation meanings and interests, the thesis intends to verify how media communication has acted in such space and what media aspects do to scientific invention. The analysis comes to the conclusion that the laborat
Keywords: campos sociais; espaço social; inovação; processos midiáticos; innovation; social fields; social space; media processes; Ciências Sociais Aplicadas